Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai di Kantor Camat Padang Utara - Tamara, Salsabila; Jumiati, Jumiati (Policy, Law and Political Research Center, 2024)
This study aims to measure the influence of work motivation and work environment on employee performance at the North Padang Sub-District Office. This study uses an associative quantitative method with a saturated sampling approach, where all employees of the sub-district office are sampled. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results showed that work motivation and work environment significantly influenced employee performance, with an R square value of 0.770. This indicates that 77% of the variability in employee performance can be explained by work motivation and work environment. In comparison, the remaining 23% is influenced by other variables not examined in this study.